Le sujet et l’auteur ou lire « l’autre femme » - Collin, Françoise (Les cahiers du CEDREF, 1990)
La réflexion que j'ébaucherai ici est issue de mon trouble devant une question qui m'a été récemment posée, qui est souvent posée aux femmes qui écrivent, et qu'elles se posent : « est-ce que tu écris en tant que femme ? ». De toute évidence la question ne porte pas sur le fait de savoir si c’est une femme qui écrit - puisqu’elle le présuppose - mais si cette femme écrit « en tant que femme ». Elle implique donc qu'une femme pourrait ne pas écrire « en tant que femme », que le sujet et l'auteur ne coïncident pas nécessairement, qu'elles entretiennent des rapports pour le moins incertains et variables.
https://doi-org.proxy.bibliotheques.uqam.ca/10.4000/cedref.1376
Keywords: cours; cycles supérieurs; discipline; fem9000; philosophie; ressource en ligne; sciences humaines; thématiques; écriture des femmes*

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Gender and knowledge: Elements of a postmodern feminism - Hekman, Susan J. (Northeastern University Press, 1990)
The aim of the book is to explore the connection between two perspectives that have had a profound effect upon contemporary thought: post-modernism and feminism. Through bringing together and systematically analysing the relations between these, Hekman is able to make a major intervention into current debates in social theory and philosophy. The critique of Enlightenment knowledge, she argues, is at the core of both post-modernism and feminism. Each also offers a basis for critical reflections about the other. In particular, post-modern philosophy provides a means of criticizing aspects of contemporary feminism and thus contributing to the development of a more sophisticated approach to current feminist issues.
Keywords: 1700-1799; 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; études culturelles

Feminism/postmodernism - Nicholson, Linda J. (Routledge, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis